2022
DOI: 10.1093/ijpp/riac073
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal cannabis for patients with chronic non-cancer pain: analysis of safety and concomitant medications

Abstract: Objectives This study aimed to explore the incidence of adverse events (AEs) reported by patients when initiating medicinal cannabis treatment for chronic pain, and the association of cannabis constituents, dose and concomitant medicines with AE incidence. Methods Patient demographics, cannabis products and AE data were collected as part of the Cannabis Access Clinics Observational Study, and concomitant medicines were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Unlike CBD, THC is well known for its increased risk of impairment [ 44 , 45 ], particularly when combined with other sedatives [ 20 ]. Nonetheless, our analyses revealed that patients on prescribed opioids and/or antipsychotics, drugs with sedating properties, are significantly more likely to be receiving THC-dominant or T+C products (70%) than CBD-dominant (30%) products, OR = 2.2 (1.0,4.6); perhaps suggesting a failure to investigate safer alternatives or inadequate attention to potential drug-drug interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike CBD, THC is well known for its increased risk of impairment [ 44 , 45 ], particularly when combined with other sedatives [ 20 ]. Nonetheless, our analyses revealed that patients on prescribed opioids and/or antipsychotics, drugs with sedating properties, are significantly more likely to be receiving THC-dominant or T+C products (70%) than CBD-dominant (30%) products, OR = 2.2 (1.0,4.6); perhaps suggesting a failure to investigate safer alternatives or inadequate attention to potential drug-drug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our analyses revealed that patients on prescribed opioids and/or antipsychotics, drugs with sedating properties, are significantly more likely to be receiving THC-dominant or T+C products (70%) than CBD-dominant (30%) products, OR = 2.2 (1.0,4.6); perhaps suggesting a failure to investigate safer alternatives or inadequate attention to potential drug-drug interactions. Conversely, the primary concern with CBD is its risk of interaction with CYP450 metabolised drugs, particularly those engaging CYP3A4, CYP2C9 and CYP 2C19 [ 20 , 21 , 44 , 46 , 47 ]. CYP3A4 enzymes [ 21 ] are responsible for the metabolism of benzodiazepines including alprazolam, midazolam and clobazam; and for part of the metabolism of other benzodiazepines including diazepam and flutrinazepam [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common AEs reported in this study were dry mouth, somnolence, fatigue, and dizziness; consistent with other studies. 29 An Australian study that recruited 1302 participants who had been taking medicinal cannabis and reported AEs found that the most common AE was increased appetite, followed by somnolence, ocular irritation, and a lack of energy. 30 The incidence of AEs was much higher in this sample; however, the most common AEs were similar to those observed in our study.…”
Section: Discussionmentioning
confidence: 99%